Delesi Gen APOBEC3B pada Pasien Human Immunodeficiency Virus di RSUD Dr. Moewardi Surakarta - Ekkim Al Kindi; Afiono Agung Prasetyo; Yulia Sari (Nexus Biomedika, 2014)
Background:HIV infection on human can get inhibition from intrinsic factor. Human can produce antivirus protein which is encoded by APOBEC3 gene. APOBEC3B (A3B) is one of APOBEC3 protein, which cannot be degradated by HIV vif protein. Therefore A3B protein is a potent inhibitor of HIV replication. But, A3B gene can get a deletion, which can decrease its effect in inhibiting HIV infection.The aim of this study was to find correlation between CD4 cells count in A3B gene deletion-positive respondents and A3B gene deletion-negative respondents. Methods: There were 51 HIV patients in Dr. Moewardi General Hospital Surakarta on November 2011, which were included as our respondents. We take respondentss blood and were isolated their DNA. Then, we run in PCR with deletion primer (Deletion_F dan Deletion_R) to detect if there was a deletion in A3B gene sequence. We run electrophoresis in 1% agarose gel with Loading Quick ?X174/HaeIII 72-1353bp as a marker. Then, we visualized the gel on Gel Documentation and was interpreted. Data of A3B gene deletion, respondentss description, HIV RNA detection, and CD4 cell count were analysed with Chi Square. Results:About 36 respondents (70.6%) were positive for deletion in A3B gene. Four of them were positive for HIV RNA detection. The average of CD4 cells count in respondents, who were positive for A3B gene deletion, was 426.86 407.4 cells/l and the others were 496.93 573.0 cells/l (p = 0.782). There were no correlation (p > 0.050) between A3B gene deletion in female respondents and CD4 cells count. A3B gene deletion was more likely to be found in female respondents (OR = 2.286; 95% CI : 0.669 7.808). Conclusions:There were no differences between the average of CD4 cell counts in A3B gene deletion-positive respondents and A3B gene deletion-negative respondents. Keywords:Polymorphism, Deletion, APOBEC3B, HIV